Pengaruh Profitabilitas, dan Leverage Terhadap Pengungkapan Emisi Karbon - Solekhah; Ickhsanto Wahyudi (CV. Multi Kreasi Media, 2022)
This study aims to determine the effect of profitability and leverage on the disclosure of carbon emissions in non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period, either partially or simultaneously. In this study, the independent variables used are profitability as proxied by Return On Asset (ROA), leverage with Debt to Total Asset Ratio (DAR), and the dependent variable is carbon emission disclosure. The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The research sample is 13 companies with a research period of 3 years, resulting in 33 samples obtained by purposive sampling technique. The data analysis method used is multiple linear regression analysis with SPSS version 26 program. The results show that the profitability and leverage variables simultaneously influence the disclosure of carbon emissions. Partially, the profitability variable has no effect on the disclosure of carbon emissions, partially leverage has an effect on the disclosure of carbon emissions.